Y-TZP surface treatments and their effects on the bond strength to resin cement - Michele Mirian May; Ana Maria Estivalete Marchionatti; Luiz Felipe Valandro; Edson Luiz Foletto; Lucio Strazzabosco Dorneles; Liliana Gressler May (Universidade Estadual de Campinas, 2019)
Aim: This study evaluated the effect of surface treatments of yttria-stabilized tetragonal zirconia polycrystal (Y-TZP) ceramics on their bond strength to a resin cement. Methods: Seventy zirconia blocks (6 × 6 × 2 mm3, IPS e.max ZirCAD) were assigned into 7 groups (n=10) - as-sintered (AS), no treatment; tribochemical silica coating + silanization (TBS; Cojet-sand; ProSil); airabrasion with 45 μm alumina particles + universal primer (AAP; Monobond®Plus); fusion sputtering (FS); SiO2 nanofilm + silanization (SN; ProSil); FS+SN+ silanization (FSSN; ProSil); FS+SN+Universal Primer (FSSNP; Monobond®Plus). Afterwards, a resin cement (RelyX™ ARC) was applied inside cylinders (Ø = 0.96 mm × 1 mm height) placed on the zirconia surfaces. Microshear bond strength tests (μSBS) were carried out (1 mm/min). Failure and phase transformation analysis were performed. Bond strength data (MPa) were subjected to Kruskal-Wallis/Mann Whitney tests. Results: TBS (27 ± 1.2) and AAP (24.7 ± 0.8) showed higher bond strengths than the other groups, followed by FSSNP (15.5 ± 4.2) and FSSN (13.3 ± 3.6). FS (3.4 ± 0.44) and SN (9.5 ± 2.7) showed the lowest values (p < 0.001). Most of the specimens exhibited an adhesive failure. Conclusion: Air-abrasion by silica-coated alumina particles followed by silanization or by alumina particles followed by universal primer resulted in the highest resin bond strength to zirconia. Fusion sputtering and silica nanofilm deposition induced low strengths. However, when these methods are applied in combination and with a primer (FSSN and FSSNP), higher bond strengths may be achieved. Low bond strengths are obtained when no zirconia treatment is performed.